Uma proposta didática de matemática para o ingresso do ensino médio - SUNBULAT, José Francisco de Oliveira (Universidade Federal do Oeste do Pará, 2024)
This research aims to present a didactic proposal based on the skills students should have when entering high school, teachers' perceptions and the BNCC Mathematics. For this was made a survey of references on; teaching, assessment and related subjects. A single question was also applied to eight state school teachers in Santarém - PA. The data collected were interpreted through content analysis and organized according to the BNCC thematic units. Teachers' perceptions are similar to the results of Prova Brasil. According to the formative needs of the students presented by the teachers, a didactic proposal was elaborated, addressing the necessary skills.